Exploring Collective Intelligence Games With Design Science: A Citizen Science Design Case - Nathan Prestopnik; Kevin Crowston (2011)
Citizen science is a form of collective intelligence where members of the public are recruited to contribute to scientific investigations. Citizen science projects often use web-based systems to support collaborative scientific activities, but finding ways to attract participants and confirm the veracity of the data produced by non-scientists are key research questions. We describe a series of web-based tools and games currently under development to support taxonomic classification of organisms in photographs collected by citizen science projects. In the design science tradition, the systems are purpose-built to test hypotheses about participant motivation and techniques for ensuring data quality. Findings from preliminary evaluation and the design process itself are discussed.